Microbial degradation of Sodium Trifluoroacetate under aerobic and anaerobic conditions - Alexandrino, Diogo A. M. (2014)
The extensive use of hydrofluorocarbons (HFCs) and hydrochlorofluorocarbons (HCFCs) as environmental acceptable alternatives to chlorofluorocarbons (CFCs) has been responsible for the introduction in the environment of significant amounts of Trifluoroacetate (TFA). Specifically, TFA is produced by the atmospheric breakdown of HCFC-123, HCFC-124, HFC-134a and HFO-1234yf, which undergo oxidative, photolytic and hydrolytic reactions to generate the compound. TFA is a highly persistent, water soluble and extremely stable fluorinated compound, that tends to accumulate in low-streamed aquatic environments, with marine ecosystems as its ultimate environmental sink. Although it does not exert considerable toxicological effects neither in microbial communities, nor in aquatic organisms, it reveals a mild toxicity regarding plants (Boutonnetet al. , 1999). There are no reports on the aerobic biodegradation of TFA, but the mineralisation of the compound by anaerobic methanogenic bacteria was demonstrated in few studies (Visscher, et al ., 1994; Kim et al., 2000).